2008
DOI: 10.1186/1471-2474-9-131
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the Mulligan Sustained Natural Apophyseal Glide (SNAG) mobilisation in the lumbar flexion range of asymptomatic subjects as measured by the Zebris CMS20 3-D motion analysis system

Abstract: Background: Mulligan's mobilisation techniques are thought to increase the range of movement (ROM) in patients with low back pain. The primary aim of this study was to investigate the application of the Mulligan's Sustained Natural Apophyseal Glide (SNAG) technique on lumbar flexion ROM. The secondary aim was to measure the intra-and inter-day reliability of lumbar ROM employing the same procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 86 publications
1
39
0
Order By: Relevance
“…Range of motion was investigated in 4 out of the 5 studies. It was improved in 3 of them 10,25,26 ; no change was reported in the fourth trial by Moutzouri et al 21 The increase in ROM was reported only in the studies performed on LBP patients, and no improvement was reported when applied on healthy participants.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Range of motion was investigated in 4 out of the 5 studies. It was improved in 3 of them 10,25,26 ; no change was reported in the fourth trial by Moutzouri et al 21 The increase in ROM was reported only in the studies performed on LBP patients, and no improvement was reported when applied on healthy participants.…”
Section: Introductionmentioning
confidence: 92%
“…21,26,35,36 Some of the available reports cannot be used for generalization because of the limitations encountered in the study design. 23,37 Therefore, the purpose of this study was to investigate the effect of adding Mulligan concept lumbar SNAG to a conventional LBP program on RE, pain, and function compared with a conventional LBP program alone in patients with chronic nonspecific LBP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies highlight how minimal treatment doses can produce clinically significant outcomes. However, research has shown that grade IV mobilisation produce greater mean force (Silvernail et al 2011) and increased plastic deformation of connective tissue (Bonutti et al, 1994;Moutzouri et al, 2008;Ulrich et al, 2010) than grade III techniques. This is of particular importance when improvements in ROM are sought within asymptomatic individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Now for the improvement of ROM other possible mechanism rather than pain mechanism is explained by some researchers. Mulligan proposed that when an increase in pain-free range of movement occurs with a SNAG it is primarily the correction of a positional fault at the zygapophyseal joint, although a SNAG also influences the entire spinal functional unit [13].One study conducted by Maria Moutzouri (2008) [21], examined the effect of Lumbar SNAGS in asymptomatic subjects and did not found any significant improvement in lumbar flexion ROM. On the other hand Self SNAGS were also found to be effective in treatment reducing pain and disability and improving cervical ROM in the study conducted by Shilpi Chhabra et al (2008),among Computer professionals.…”
Section: To Study the Effect Of Muscle Energy Technique Versus Mulligmentioning
confidence: 99%